Rehabilitation of speech among patients laryngectomized due to laryngeal carcinoma - Wójtowicz-Chomicz, Katarzyna; Bartnik, Beata; Borzęcki, Andrzej (Polish Journal of Public Health, 2012)
Introduction. Laryngeal carcinoma is the most frequent cancer of head and neck. Available literature confirms smoking cigarettes as the most common habit among patients affected with laryngeal and pharyngeal cancer. Despite many symptoms, patients with laryngeal carcinoma rarely refer to hospital and therefore, due to intensive extension of tumor, patients have to be cured with serious surgeries. As a result of larynx removal and loss of phonation organ, patients are unable to communicate verbally. Rehabilitation in case of larynx resection aims to regain speech abilities and bring back patients to the normal social life. Patients also do concern about quality of their life once treatment is accomplished.Aim. Evaluation of rehabilitation progress among laryngectomized patients treated with various techniques enabling to use speech organ in everyday life.Material and methods. Studies were conducted among 151 patients with laryngeal carcinoma subjected to larynx removal operation. Patients were hospitalized in the laryngological departments in macro-region of Lublin.Results. Majority – 88.08% of patients subjected to operation of larynx removal followed phonetic and logopedic rehabilitation. However, only 22% of patients followed instructions given by phoniatrist regarding aspects of speech therapy.Conclusions. Esophageal speech efficient for basic contact with society was mastered by almost half of patients reaching 57.89 %. Pseudo-whisper was followed by 34.58% of patients, being recognized only by the closest members of society. Writing and gesticulation refers to 7.53% of patients, whereas 11.25% of patients use electrolarynx. Rehabilitation procedures are irregularly followed by patients; patients do not devote enough time for rehabilitation procedures.